2019
DOI: 10.1186/s13041-019-0449-0
|View full text |Cite|
|
Sign up to set email alerts
|

Region- and time-dependent gene regulation in the amygdala and anterior cingulate cortex of a PTSD-like mouse model

Abstract: Posttraumatic stress disorder is developed by exposure to a threatening and/or a horrifying event and characterized by the presence of anxiety, hyperarousal, avoidance, and sleep abnormality for a prolonged period of time. To elucidate the potential molecular mechanisms, we constructed a mouse model by electric foot shock followed by situational reminders and performed transcriptome analysis in brain tissues. The stressed mice acquired anxiety-like behavior after 2 weeks and exaggerated startle response after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 79 publications
(76 reference statements)
2
22
0
Order By: Relevance
“…Previous work shows that decreased GABAergic functioning in the amygdala can directly lead to altered performance on the OFT, EPM, and fear conditioning (Babaev et al, 2018). Further, Adcy8 codes for a protein kinase that has been repeatedly implicated in anxiety-like behavior, synaptic plasticity, and mood disorders (Schaefer et al, 2000;de Mooij-van Malsen et al, 2009;Bernabucci and Zhuo, 2016;Tanaka et al, 2019). A recent study found changes in anxiety-like behavior linked to a rodent PTSD-like model accompanied by aberrant Adcy8 expression in the amygdala (Tanaka et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work shows that decreased GABAergic functioning in the amygdala can directly lead to altered performance on the OFT, EPM, and fear conditioning (Babaev et al, 2018). Further, Adcy8 codes for a protein kinase that has been repeatedly implicated in anxiety-like behavior, synaptic plasticity, and mood disorders (Schaefer et al, 2000;de Mooij-van Malsen et al, 2009;Bernabucci and Zhuo, 2016;Tanaka et al, 2019). A recent study found changes in anxiety-like behavior linked to a rodent PTSD-like model accompanied by aberrant Adcy8 expression in the amygdala (Tanaka et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Adcy8 codes for a protein kinase that has been repeatedly implicated in anxiety-like behavior, synaptic plasticity, and mood disorders (Schaefer et al, 2000;de Mooij-van Malsen et al, 2009;Bernabucci and Zhuo, 2016;Tanaka et al, 2019). A recent study found changes in anxiety-like behavior linked to a rodent PTSD-like model accompanied by aberrant Adcy8 expression in the amygdala (Tanaka et al, 2019). Similar to our results, the stress-induced change in Adcy8 expression was dependent on a time delay following the stressor, highlighting the importance of the treatment by timepoint interaction in regulating brain function and behavior after a stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially methylated genes in the vHPC included Fkbp5 , Ksr1 , and Pnpla2 . Interestingly, Fkbp5 and Ksr1 transcription was disrupted in one behavioral mouse model of PTSD, 57 where mice were exposed to an electric footshock and then presented situational reminders. Fkbp5 encodes a glucocorticoid receptor chaperone whose functioning has been associated with a maladaptive prolonged stress response in individuals with PTSD and other anxiety disorders 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of PTSD involving animal models often examined fear conditioning or fear extinction [ 4 ]; however, the present study used the situational reminder procedure with the traumatic memory associated with the context. This kind of study was aimed at mimicking the reexperiencing of a traumatic memory of PTSD symptoms in humans [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%